Why do schooling returns differ so much?: observations and puzzles from Thailand and the Philippines - Yamauchi, Futoshi (Asian Development Bank, 2003)
This paper examines returns to schooling in Thailand and the Philippines, using recent employee surveys in some manufacturing industries. First, we find that schooling returns differ between the countries, with position, job type, and firm fixed effects being controled. Moreover, the returns increase stably as education attainment increases in Thailand, whereas the returns increase only at university and post-graduate levels in the Philippines. The concavity - convexity puzzle should be related to overall conditions of the labor markets. Second, private school premiums are higher in the Philippines than Thailand. Whatever the reason is, this finding is consistent with the dominance of private institutions in the Philippine education system. Third, we also find that school quality of high school education matters to wages in the Philippines. Both labor — market equilibrium conditions, intra-firm human resource management as well as selection mechanism in education system may differ between the countries, which explain differences in schooling return structure.